2012
DOI: 10.1002/aqc.2254
|View full text |Cite
|
Sign up to set email alerts
|

The role of pond management for biodiversity conservation in an agricultural landscape

Abstract: Debate surrounds the best way to deal with pond terrestrialization so as to maximize landscape-scale biodiversity. One way of addressing this issue is to re-set succession via management activities, but the merits of this approach relative to non-intervention and pond creation are little known. Manor Farm in Norfolk, UK, possesses around 40 ponds, and each year three to four ponds are subject to management involving tree (de-shading) and/or sediment removal. To determine the consequences of management for pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(139 citation statements)
references
References 34 publications
2
137
0
Order By: Relevance
“…diameter), shallow (generally \ 1 m) and, in the case of the farmland ponds, largely alkaline and eutrophic (Table 1). Further details on the history, geography and ecology of ponds in the study area are given in Sayer et al (2012).…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…diameter), shallow (generally \ 1 m) and, in the case of the farmland ponds, largely alkaline and eutrophic (Table 1). Further details on the history, geography and ecology of ponds in the study area are given in Sayer et al (2012).…”
Section: Study Sitesmentioning
confidence: 99%
“…While a number of palaeo-studies have been undertaken in arctic ponds (Douglas and Smol 1994;Keatley et al 2011;Bouchard et al 2012;Stewart et al 2013), few if any studies have focused on temperate European lowland ponds-as in this study. Nonetheless, in recent years, a number of studies have shown the predominantly agricultural pond resource of lowland Europe to be of major importance in terms of aquatic biodiversity conservation (Ruggiero et al 2008;Sayer et al 2012), aquatic-terrestrial energy subsidies (Davies et al 2016) and carbon sequestration (Downing et al 2008), among other roles. Given increasing interest in pond conservation, palaeoecology could have an important role in inferring longterm changes in pond ecology and function in response to environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Norfolk land owners and farm owners are vitally important for the continued survival of pondscapes as the majority of ponds are located in agricultural settings (Boothby et al, 1995a;Sayer et al, 2012).…”
Section: Agricultural Pondsmentioning
confidence: 99%
“…Although some individual agricultural ponds in the Astarac region were species poor, they still contributed to the overall regional/pondscape diversity (Céréghino et al, 2008a). Agricultural ponds in Norfolk, UK, supported 57 taxa, and evidence suggested the careful management of farm ponds elevated the invertebrate biodiversity at both an alpha (individual) and gamma (regional) scale (Sayer et al, 2012). In addition, a total of 76 freshwater beetle taxa (one third of the national species pool) were recorded from 54 ponds in intensively farmed regions in Ireland (Gioria et al, 2011).…”
Section: Agricultural Pondsmentioning
confidence: 99%
See 1 more Smart Citation